Reusam idang meulapeh in commemorating the prophet's Maulid tradition: a study in the Pidie District, Aceh Province, Indonesia - Lasri Lasri; R Roslina; R Riswan (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
This research aims to improve the preservation of Reusam Idang Meulapeh and the symbol of the Idang Meulapeh reusam tradition in commemorating the Prophet's maulid in the Pidie region. The research used a qualitative descriptive method. Data sources were obtained in the form of primary data and secondary data. Data collection techniques were carried out by observation, interview, and verification or conclusion drawing. The population in this study was the people of Pidie. The sampling technique was carried out in 5 villages in the Pidie area totaling 25 people, including 5 people from Pangge Pilok village, 5 people from Mesjid Reubee village, 5 people from Neulop village, 5 people from Keude Keulibeut village and 5 people from Kampong Pukat. The results of the study that the implementation of the Nadi maulid tradition in the Pidie region for 3 months a year and the process of the maulid implementation tradition with several stages including preparation of idang meulapeh, meudikee and Islamic preaching at night. The tradition of the Prophet's Maulid is carried out in the month of 12 Rabiul Awal to the beginning of the month of Jumadil Akhir.  A unique tradition at the time of commemorating the Prophet's maulid, the local community serves a variety of traditional culinary delights. One of them is Idang Meulapeh, which is a mandatory tradition in every Prophet's meulod khanduri. For the people of Pidie, the celebration of the Prophet's birthday without Idang Meulapeh is incomplete, because Idang Meulapeh is one of the special traditions in commemorating the Prophet's birthday. From the preparation of food in people's homes called Bu Kulah (rice wrapped in leaves), Idang Meulapeuh (a storied dish) will be brought to Meunasah / Mosque around 11:00 to eat together with residents, orphans and guests of other village and Mukim neighbors. Before eating the food that is served, the community first prays to our king the prophet Muhammad SAW. Idang meulapeh is also a fairly expensive dish, with that not all circles this reusam can be done. Only some areas in Aceh still apply the idang meulapeh tradition. For this reason, this research is very important to preserve the Idang Meulapeh reusam tradition in commemorating maulid in the Pidie region. Therefore, the purpose of the community in providing various kinds of food menus in Idang Meulapeh and honoring the birth month of the Prophet Muhammad SAW.